Effect Of Concentration Metal Precursor Co And Mo On Character Of CoMo / USY Catalyst - Nugrahaningtyas, Khoirina Dwi; Hidayat, Yuniawan; Saputri, Tiara Diah (ALCHEMY Jurnal Penelitian Kimia, 2014)
The preparation and characterization of bimetallic catalysts using impregnation method with a variation of concentration of precursor sequence Co and Mo metal  obtained  catalyst K 1 [Co (0.018 M) - Mo (0.037 M)/USY]. K 2 [Co (0.026 M) - Mo (0.055 M)/USY], K 3 [Co (0.035 M) - Mo (0.074 M)/USY], K 4 [Co (0.05 M) - Mo (0.11 M )/USY] and K 5 [Co (0.107 M) - Mo (0.22 M)/USY].Character of the catalyst in terms  of crystallinity was analyzed by XRD. The result shows that there is no cristalinity damage of USY after impregnation but the amorphous cristalin structure was obtained.  Amount of metal content was analyzed by XRF and the catalyst morphology by SEM-EDS. The result shows that the higher the concentration of Co and Mo so that find the higher content of metal in catalyst of the prepared catalyst increase. K 4 shows the best characteristic of catalysts prepared in this research. Analysis of K 4 is proving that Co and Mo are presented in catalyst